Las redes sociales como plan de marketing en el desarrollo turístico cantón Balzar, año 2020 - Flores Bone, Johnny Xavier (2021)
The objective of this research work is to analyze the innovations and advantages of tourism promotion through internet media such as social networks, public management websites of tourist destinations in the Balzar Canton, Los Ríos Province. In addition to that, the importance of adopting a marketing strategy that implements the media, social networks and search engines in the online tourism promotion that reflect in states and regions, public and private organizations is presented. Through the marketing plan, there is interest in disseminating information about the Balzar Canton, its destination and private organizations involved in the tourism production chain such as hotels, tour operators, travel agencies, transporters, restaurants, among others, seeking to promote their products and services. According to Biz, one of the main problems that will arise when applying this method is access to information and the ability to process it for operational and strategic use. Information, consumer and service provider culture are also reflected in habits, values and different customs and affect the way in which information is treated, transmitted and shared.